2022
DOI: 10.1158/0008-5472.can-21-1225
|View full text |Cite
|
Sign up to set email alerts
|

Dll1-Mediated Notch Signaling Drives Tumor Cell Cross-talk with Cancer-Associated Fibroblasts to Promote Radioresistance in Breast Cancer

Abstract: Resistance to radiotherapy is a major obstacle for effective cancer treatment. Both cancer-associated fibroblasts (CAF) within the tumor microenvironment (TME) and Notch signaling are implicated in radioresistance, but their potential interrelationship is unclear. Here, we report that irradiated samples obtained from luminal breast cancer patient tumors express higher levels of the Notch ligand Dll1 and have a greater number of αSMA- and FAP-expressing activated CAFs. Single cell transcriptomic profiles furthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…In breast cancer, exosomal miR‐221 secreted by CAFs decreased ER expression and upregulated Notch3 expression in recipient cancer cells, which induced the production of CD133‐overexpressing CSCs and ultimately promoted hormone therapy resistance [ 211 ]. Additionally, DLL1 + breast cancer cells recruited CAFs and promoted Wnt ligand secretion by Notch2/3‐expressing CAFs, resulting in increased Wnt/β‐catenin‐dependent DLL1 + CSC functions to promote metastasis and radioresistance [ 212 ].…”
Section: Significance Of Signaling Pathways In Cafsmentioning
confidence: 99%
“…In breast cancer, exosomal miR‐221 secreted by CAFs decreased ER expression and upregulated Notch3 expression in recipient cancer cells, which induced the production of CD133‐overexpressing CSCs and ultimately promoted hormone therapy resistance [ 211 ]. Additionally, DLL1 + breast cancer cells recruited CAFs and promoted Wnt ligand secretion by Notch2/3‐expressing CAFs, resulting in increased Wnt/β‐catenin‐dependent DLL1 + CSC functions to promote metastasis and radioresistance [ 212 ].…”
Section: Significance Of Signaling Pathways In Cafsmentioning
confidence: 99%
“…The Notch signaling pathway is a highly evolutionarily conserved stemness-related pathway. In breast cancer, Notch signaling drives crosstalk between tumor cells and CAFs to promote the radio-resistance of tumor cells [ 40 ]. Here, our data indicated that CAF-derived STC1 could activate the Notch1 signaling pathway in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Production of TGFβ by radio-treated CAFs can also promote cancer cell aggressive and invasive properties, acting as a radiotherapy therapeutic escape and resistance ( Papadopoulou and Kletsas, 2011 ; Zhang et al, 2017 ). Notch signaling in CAFs plays a role in radioresistance, as demonstrated by a recent study that identified single-cell transcriptomic profiles in CAF subpopulations in delta-like canonical Notch ligand 1 , Dll1⁺ tumors ( Nandi et al, 2022 ). The connection between Notch signaling and CAF-associated metastasis and radioresistance could be exploited to improve breast cancer patient outcomes by minimizing radioresistance and stemness ( Nandi et al, 2022 ).…”
Section: Role Of Cafs In Therapy Resistancementioning
confidence: 99%
“…Notch signaling in CAFs plays a role in radioresistance, as demonstrated by a recent study that identified single-cell transcriptomic profiles in CAF subpopulations in delta-like canonical Notch ligand 1 , Dll1⁺ tumors ( Nandi et al, 2022 ). The connection between Notch signaling and CAF-associated metastasis and radioresistance could be exploited to improve breast cancer patient outcomes by minimizing radioresistance and stemness ( Nandi et al, 2022 ). The increased expression of CXCL12, TGFβ, MMPs, and HGF in CAFs induced by radiation increases the activation of EMT pathways in cancer cells ( Ansems and Span, 2020 ).…”
Section: Role Of Cafs In Therapy Resistancementioning
confidence: 99%